STUDI FAAL PARU DAN FAKTOR DETERMINANNYA PADA PEKERJA DI INDUSTRI SAWMILL - Ulfa Hikmayanti (Universitas Airlangga, 2018)
Sawmill industry processes log into sawmill and also results wood dust as by-product . Dust can be potentially inhaled by workers and cause impaired lung function. In addition, several other factors can effect lung function such as age, body mass index status, smoking habit and using respiratory protective equipment habits. The purpose of this study was to describe lung function on workers in sawmill industry and the determinant factors. This research was an observational type with descriptive method. This study used total population with 36 workers. The data were obtained from interview, dust measurement, body mass index measurement and lung function test, meanwhile the instruments were questionnaire, high volume dust sampler (hvds), microtoise, weight scale and spirometer. This data were analyzed by cross tabulation. The results of this study showed that the time weighted average concentration in UD. Sinar Abadi was 1.59 mg/m3, meanwhile spirometry test showed 42.8% had normal lung function and 52.8% had impaired lung function. Workers who had impaired lung function were 64.7% exposed to doses >5mg/m3.tahun, 60% were >44 years old, 100% were obese, 69.9% were smoker and 76.5% never used respiratory protective equipment. The time weighted average concentration was above from threshold limit value and most of the workers had impaired lung function. Workers with impaired lung function are more likely to be exposed to dose >5mg/m3.years, older, obese, smoker, and didn’t use respiratory protective equipment. Keywords: determinant factors, lung function, wood dust